2013
DOI: 10.4248/br201301004
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Overview of Skeletal Phenotypes Associated with Alterations in Wnt/β-catenin Signaling in Humans and Mice

Abstract: The Wnt signaling pathway plays key roles in differentiation and development and alterations in this signaling pathway are causally associated with numerous human diseases. While several laboratories were examining roles for Wnt signaling in skeletal development during the 1990s, interest in the pathway rose exponentially when three key papers were published in 2001-2002. One report found that loss of the Wnt co-receptor, Low-density lipoprotein related protein-5 (LRP5), was the underlying genetic cause of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 423 publications
2
85
0
Order By: Relevance
“…Members of the Dikkopf (DKK) family, secreted Frizzled-related proteins (sFRP), and Wnt inhibitory factor 1 (WIF-1), act as antagonists of Wnt signaling [55]. Mouse genetic studies have shown that Wnt signaling is intimately involved in the development of many tissues and organs, and both gain- and loss-of-function mutations in Wnt signaling cause various human diseases, including bone diseases [56] [57, 58]. …”
Section: Wnt/β-catenin Signalingmentioning
confidence: 99%
See 2 more Smart Citations
“…Members of the Dikkopf (DKK) family, secreted Frizzled-related proteins (sFRP), and Wnt inhibitory factor 1 (WIF-1), act as antagonists of Wnt signaling [55]. Mouse genetic studies have shown that Wnt signaling is intimately involved in the development of many tissues and organs, and both gain- and loss-of-function mutations in Wnt signaling cause various human diseases, including bone diseases [56] [57, 58]. …”
Section: Wnt/β-catenin Signalingmentioning
confidence: 99%
“…Multiple Wnt ligands signal through non-canonical pathways, including the planar cell polarity (PCP) and the Wnt/Ca 2+ pathways [57]. Non-canonical Wnt signaling has been implicated in promoting chondrocyte differentiation due to its ability to inhibit canonical Wnt signaling.…”
Section: Wnt/β-catenin Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Wnt signaling has emerged as a major promoter of bone accretion 38 . Recently, Wnt proteins were shown to reprogram cellular glucose metabolism during osteoblast differentiation 39 .…”
Section: Wnt Stimulates Aerobic Glycolysis During Osteoblast Differenmentioning
confidence: 99%
“…Both TGF-β and Wnt signal pathways have been implicated in cancer progression and EMT [18]. TGF-β1 has been shown to highly express in ACC patient samples and SACC-LM cell line and induced Smad2 phosphorylation and promoted the migration and invasion of SACC-83 cells [19].…”
Section: Introductionmentioning
confidence: 99%